Data Warehouse Design with Kimball Method: Case Study of Fahrenheit Manufacturing Systems - Widianty Widianty (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Competition in the business world that increasingly stringent requires management to make decisions accurately and quickly. It is also felt by Farhenheit as entrepreneurs. To achieve thier forte in competing in theglobal competition, he needs systems like strategic decision makers which is up-to-date reliable and fast. Then the solution of area manufatur datawarehouse design is necessary to support the above objectives,i.e. : the right and fast decisions. However, Fahrenheit only has ERP as their core system currently and they do not have management support system. They have some difficulty to understand some problems and do better analysis. There are some datawarehouse development methodologies. Methods that will be used for the development of datawarehouse design is Kimball Method. Kimball method was chosen because of its development process that follows the business process is very suitable for the development of datawarehouse gradually to a company.Kimball's method gives a mart for the related business processes.This study is conducted by interview and survey from several senior managers and directors in Fahrenheit to know about their requirement and how they do analysis currently.